The Verbs Synonyms of Batubara Malay Language in North Sumatera Province - Julisah Izar; Rengki Afria (Proceeding International Conference on Malay Identity, 2020)
The aims of this research to describe the synonyms of Batubara Malay language verbs north Sumatera Province. This research used descriptive qualitative approach. The techniques of collecting data in this research used unstructured interviews and recording techniques, while data analysis techniques in this research used the concept of Miles and Huberman, namely data collection, reduction, classification and drawing conclusions. The results showed that there are two kinds of verb synonym form of Batubara Malay language, north Sumatera Province, those are total and complete synonym and total and not complete synonym.Keywords: synonymy, verb, Batubara Malay Language, North Sumatera.